2011
DOI: 10.1016/j.vaccine.2011.09.071
|View full text |Cite
|
Sign up to set email alerts
|

Influenza associated mortality in the subtropics and tropics: Results from three Asian cities

Abstract: Influenza has been well documented to significantly contribute to winter increase of mortality in the temperate countries, but its severity in the subtropics and tropics was not recognized until recently and geographical variations of disease burden in these regions remain poorly understood. In this study, we applied a standardized modeling strategy to the mortality and virology data from three Asian cities: subtropical Guangzhou and Hong Kong, and tropical Singapore, to estimate the disease burden of influenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
64
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 29 publications
1
64
1
Order By: Relevance
“…3, 4, 5, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23 Notably, our study observed that influenza B caused the highest burden (20.5 [CI 14.2‐34.9] per 100 000) when influenza B virus predominated in 2007/2008. This mortality pattern is consistent with those described in studies conducted by China CDC and Guangzhou CDC,3, 5 but differs from studies conducted in other regions such as Hong Kong,14 Singapore,16 Thailand,17 United States,18, 19 and New Zealand,23 where the highest death rates were associated with influenza A(H3N2).…”
Section: Discussionmentioning
confidence: 47%
“…3, 4, 5, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23 Notably, our study observed that influenza B caused the highest burden (20.5 [CI 14.2‐34.9] per 100 000) when influenza B virus predominated in 2007/2008. This mortality pattern is consistent with those described in studies conducted by China CDC and Guangzhou CDC,3, 5 but differs from studies conducted in other regions such as Hong Kong,14 Singapore,16 Thailand,17 United States,18, 19 and New Zealand,23 where the highest death rates were associated with influenza A(H3N2).…”
Section: Discussionmentioning
confidence: 47%
“…Third, because the study population included only elementary schoolchildren, children in kindergarten and junior high school were not evaluated. Fourth, influenza epidemics, even during the same season, differ among countries, suggesting that geography usually affects influenza epidemics during large-scale evaluations (31,32). Influenza epidemics are also affected by weather-associated factors, including humidity (33).…”
Section: Discussionmentioning
confidence: 99%
“…Vaccine coverage is still relatively low in Guangzhou, with an estimated 13 vaccine doses used per 100 population (45), while a pediatric study reported a 6.5% vaccination rate for pandemic H1N1/09 in a boarding school (46). The vaccine is administered around October-December in anticipation of the Northern Hemisphere winter influenza season, peaking in January or February.…”
Section: Discussionmentioning
confidence: 99%